2006
DOI: 10.1002/asi.20366
|View full text |Cite
|
Sign up to set email alerts
|

Arts and humanities literature: Bibliometric characteristics of contributions by Turkish authors

Abstract: Scholarly communication in arts and humanities differs from that in the sciences. Arts and humanities scholars rely primarily on monographs as a medium of publication whereas scientists consider articles that appear in scholarly journals as the single most important publication outlet. The number of journal citation studies in arts and humanities is therefore Researchers based at Turkish universities produced 90% of all publications. Two-thirds of references in publications were to monographs. The median age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 33 publications
1
15
0
5
Order By: Relevance
“…These are the aspects widely gathered and analysed in bibliometric studies of humanities [THOMPSON, 2002;AL, SAHINER, TONTA, 2006;NEDERHOF, 2006], which allows comparisons to be made.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are the aspects widely gathered and analysed in bibliometric studies of humanities [THOMPSON, 2002;AL, SAHINER, TONTA, 2006;NEDERHOF, 2006], which allows comparisons to be made.…”
Section: Methodsmentioning
confidence: 99%
“…These values are similar to, but even lower than, those found by previous authors dealing with the humanities (Argentine authors in the A&HCI 5.9%, Turkish authors 17%, history 7%). [MOLTENI, ZULUETA, 2002;LOWE 2003;AL, SAHINER, TONTA 2006]. It seems fairly obvious that Catalan literature follows the habitual parameters in these disciplines insomuch that authors work individually with specific aspects of research rather than collaborating with others.…”
Section: Productivity and Collaboration Of The Authorsmentioning
confidence: 99%
“…Single author was the typical style for the art exhibit reviews. The single authorship was also prevalent in arts and humanities journal articles written by authors affiliated with Turkish institutions and indexed in A&HCI (Al et al 2006). However, 'techno.seduction' an exhibition of multimedia installation work by forty artists' source was published by seven authors.…”
Section: Authorsmentioning
confidence: 99%
“…These studies predominantly cover resources indexed in SCIE and SSCI databases. Although not in the main, A&HCI has also been used for bibliometric studies, such as on the international presence of studies on Catalan literature (Ardanuy et al 2010), arts and humanities literatures in a country such as Turki (Al et al 2006), and Spain (DortaGonzález and Ramírez-Sánchez 2014). The mapping on the basis of aggregated citations for journals in A&HCI (Leydesdorff et al 2011) and citation analysis studies in the humanities (Ardanu 2013) are also reported.…”
Section: Introductionmentioning
confidence: 99%
“…To quantify the participation of different authors, many research works calculate the number of authors [e.g. (Abramo et al, 2009;Abrizah et al, 2012;Al et al, 2006;Glanzel, 2002;Hirsch, 2010;Zhou et al, 2007), etc.]. Also frequent number of research centers (Bordons & Barrigon, 1992;Montoya et al, 2014;Rojas-Sola & Jorda-Albinana, 2009a;Rojas-Sola & San-Antonio-Gomez, 2010b;Rosas et al, 2011;Voracek & Loibl, 2009) and / or number of countries participating in each article (Chen et al, 2007;Katz & Hicks, 1997;Keiser & Utzinger, 2005;Uzun, 2004).…”
Section: Quantitative Indicatorsmentioning
confidence: 99%